Coaches` dispositions and non-formal learning situations: an analysis of the `coach talent programme` - Leeder, T. M.; Warburton, V. E.; Beaumont, L. C. (Sport in Society: Cultures, Commerce, Media, Politics, 2021)
Research which identifies and describes the learning situations coaches engage with often overlooks how coaches` dispositions and the `learning cultures` they occupy influences their opportunities for learning, limiting our understanding of what `works` and for `whom`. Seven coaches from five sports were interviewed regarding their experiences of `The Coach Talent Programme` (CTP); a non-formal learning situation consisting of cross-sport CPD workshops delivered by a UK County Sports Partnership. Data were analysed thematically, integrating Pierre Bourdieu`s sociology alongside Phil Hodkinson`s theory of `learning cultures`. Three themes were developed: (1) social interaction and cross-sport learning; (2) workshop content and online learning; and (3) tutor capital and the coaching field. The findings demonstrate how coaches` `learning` within non-formal situations varies significantly due to embodied dispositions, capital, and the social fields coaches are positioned within. Sports organisations would benefit from recognising the influence of these factors to develop transformative non-formal environments for coach learning.